2009
DOI: 10.1002/ana.21652
|View full text |Cite
|
Sign up to set email alerts
|

T‐helper 17 cells expand in multiple sclerosis and are inhibited by interferon‐β

Abstract: Evidence that an expansion of peripheral Th17 cells, a Th subset that can infiltrate brain parenchyma and damage cells, is associated with disease activity in MS. The greater IFN-alphaR1 level expressed by Th17 compared with Th1 cells might make them a selective target for IFN-beta therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
283
3
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(324 citation statements)
references
References 47 publications
20
283
3
8
Order By: Relevance
“…Interestingly, these finding mirror changes as predicted by detailed in vitro mechanistic studies of IL-17 (9)(10)(11)(12)14) and . Another main finding of our study was the potential difference between responders and non-responders in IL-17A levels before and after treatment.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Interestingly, these finding mirror changes as predicted by detailed in vitro mechanistic studies of IL-17 (9)(10)(11)(12)14) and . Another main finding of our study was the potential difference between responders and non-responders in IL-17A levels before and after treatment.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, IFN-β was shown to reduce IL-17 production directly or indirectly by reduction of osteopontin and induction of IL-27 (10). Consequently, studies have demonstrated that IFN-β may exert its effect in MS by reduction of IL-17-associated immunity (11)(12)(13)(14). In contrast, it has been…”
Section: Inflammatory Effects Diminished Trafficking Of T Cells Intomentioning
confidence: 99%
“…Their role in relapsing remitting MS (RR MS) is supported by a recent report on the increased frequency of IL-17A-producing cells, which is positively associated with clinical disease activity (2). Th17 cell differentiation is orchestrated by multiple cytokines, including IL-6, IL-1b, TGF-b, IL-21, and IL-23, which stimulate Th17 cell differentiation, and IFN-g, IL-4, IL-12, IL-10, and IL-27, which inhibit Th17 cell differentiation (3).…”
mentioning
confidence: 93%
“…In multiple sclerosis (MS), IL-17 expression in CD4 + T cells within CNS lesions has been observed and more IL-17 + T cells were found in active compared with inactive lesions (6,7). Moreover, expansion of peripheral T H 17 cells during active MS, as well as enhanced frequencies of T H 17 cells in the cerebrospinal fluid during relapse, indicates that this population might be involved in disease exacerbation (8,9). Another study demonstrated increased frequencies of memory T H 17 cells in the peripheral blood of MS patients, which was further enhanced during relapse (10).…”
mentioning
confidence: 99%